(untitled) (مجلة المنصور, 2022)
This paper proposed a method of data hiding by taking advantage of the physical characteristics of computer system and how it stores document file and treating it as a compound file. The unused block in Microsoft Compound Document File Format (MCDFF) is used to hide data. The possibilities provided by Microsoft Word Processor program have also been utilized, such as Tools, to generate cover for hiding. The proposed system embeds steganography text in structure (Binary File Format) of digital and printed text document file which is a file of Microsoft Word Document file (Doc.) using two Processes: Cover Generation and Embedding Processes. Cover Generation Process: where the cover is a document of Microsoft Word Document file format 2003 (doc.) and will appear to be the product of a collaborative writing effort among authors using Track Changes tool. Embedding Process hiding text string in unused block of binary file format of that document cover. This paper proposed a new technique, which gives good results, such that the user can hide 63byte in 34KB document cover size with informed about size of empty document=10/11KB, in addition, using Track Changes tool does not affect on hidden data and no problem was detect on hidden data at stego-document mailing or copying.